2018
DOI: 10.1007/s00214-018-2255-7
|View full text |Cite
|
Sign up to set email alerts
|

Insights into conformational changes in AlkD bound to DNA with a yatakemycin adduct from computational simulations

Abstract: Structural integrity of DNA molecules is necessary for their information storage function. Cells rely on a number of pathways to ensure that the damage to DNA induced by endogenous and exogenous reagents is repaired. AlkD, a base excision enzyme, removes a damaged nucleobase by cleaving a glycosidic bond. Unlike many other base excision enzymes, AlkD does not flip a damaged nucleobase into a designated reaction pocket, and as such can repair nucleobases with larger adducts, such as yatakemycin. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The AlkD–DNA PC1 then highlights the W187–A*6 contact, which has also been demonstrated to be a main component of the AlkD repair machinery by Parsons et al Next, the Y27–A7 hydrogen bond distance between sidechain and the ring nitrogen, N3, represents one of two residues that extends from the opposite side of the AlkD-binding cleft to interact with the nucleobase 3′ to the methylation site. Although Y27 does not insert directly between base pairs of the DNA, it is a partially intercalating residue, which is generally an integral part of canonical glycosylase repair. , Moreover, Y27 is thought to play a role in the screening process, and thus this result is consistent with this hypothesis . Another DNA backbone hydrogen-bonding interaction is then seen with R26–T9, which extends along the DNA from the same α-helix as Y27.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…The AlkD–DNA PC1 then highlights the W187–A*6 contact, which has also been demonstrated to be a main component of the AlkD repair machinery by Parsons et al Next, the Y27–A7 hydrogen bond distance between sidechain and the ring nitrogen, N3, represents one of two residues that extends from the opposite side of the AlkD-binding cleft to interact with the nucleobase 3′ to the methylation site. Although Y27 does not insert directly between base pairs of the DNA, it is a partially intercalating residue, which is generally an integral part of canonical glycosylase repair. , Moreover, Y27 is thought to play a role in the screening process, and thus this result is consistent with this hypothesis . Another DNA backbone hydrogen-bonding interaction is then seen with R26–T9, which extends along the DNA from the same α-helix as Y27.…”
Section: Resultssupporting
confidence: 86%
“…12 Moreover, the scanning tyrosine of OGG1 discovered using fluorescent kinetic analysis is comparable to the αβ helix Y27, which has been proposed to be relevant to the search process. 8,28 Indeed, the Y27−A7 interaction is demonstrated here to be crucial for separating the AlkD SC from the EC. And although the exact role of Y27 in scanning nucleotides is not known, it is demonstrated that in the SC the Y27−A7 hydrogen bond is from Y27 to the O4′ ribose oxygen of A7 (Figures S11 and S12).…”
Section: ■ Methodsmentioning
confidence: 65%
See 3 more Smart Citations